Policy, government strata and sustainable tourism of a rural destination: an analytical network policy perspective - Siow, May Ling; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Taylor's University Press, 2022)
Sustainable tourism policies in rural destinations are often complex. Governments strive to ensure that the objectives of sustainable tourism are met through various strata of agencies. As a result, institutional fragmentation has become the undesirable outcome of this approach. The policy Delphi technique was employed in this study to align decision-making divergence between local, state and federal governments for sustainable tourism aspirations in Sabah, Malaysia. The results reveal vastly divergent perspectives from actors representing the triple-tier governmental system. The findings indicate that the curtailment of the policy cycle is due to knowledge gaps coupled with on-site complexities. The paper suggests that the administration of policies could be based on a system that allows timely rectification, indicating the need for a dynamic policy cycle for multi-stage amendments when on-site complexities are identified. The perspective of this paper is that of the policy-analyst, proposing an analytical network policy process that allows timely rectification of policies.